Decolorization of textile basic dye in aqueous solution by ozone - Turhan, Kadir; Durukan, Ilknur; Ozturkcan, S. Arda; Turgut, Zuhal (ELSEVIER SCI LTD, 2012)
In this study, the factors affecting the rate of chemical oxygen demand (COD) of a synthetic waste solution containing a water soluble basic dye [Methylene Blue] were investigated. Decolorization of the dye was achieved by ozonation. The research was conducted using a batch bubble column to take the advantage of the intensive back-mixing that prevails in bubble columns. As a result, the COD of basic dyestuff wastewater was reduced to 64.96% and decolorization was observed under basic conditions (pH 12), complete MB degradation occurring in 12 min. Ozone consumption continued for a further 16 min after which time most of the degradation reactions were complete. Kinetic studies showed that direct ozonation of the aqueous dyes represented a pseudo-first-order reaction with respect to the dye. The apparent rate constant, which increased with both the applied ozone dose ani higher pH values, declined logarithmically with the initial dye concentration. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Ozonation; Methylene Blue; Basic dye; Chemical oxygen demand; Kinetics; Decolorization; BUBBLE-COLUMN REACTOR; WASTE-WATER; AZO-DYE; OZONIZATION; Chemistry; Engineering; Materials Science